Experimental characterization of commercial lime based grouts for stone masonry consolidation - Luso, Eduarda (2018)
Conservation, repair and strengthening of historic masonry buildings should preserve their significance and ensure their structural stability. The condition of a given structure and the extent of damage determine the type of action needed. Grouting is a well-known remedial technique, which can be durable and mechanically efficient whilst preserving the historic value. Still, the selection of a grout for repair must be based on the physical and chemical properties of the existing materials. Parameters such as rheology, injectability and stability of the mix should be considered to ensure the effectiveness of grout injection. In addition, the bond strength of the grout to the existing material is the most relevant mechanical property. Several commercial lime based grouts are available but it is unclear what are the applicable standards and requirements. This paper evaluates the behavior of commercial grouts under laboratory conditions. First, the properties of the grouts as an independent product are assessed with the objective to perform a comparative analysis of their behavior subjected to different conditions (temperature and working time of grout after mixing). Then, the behavior of the grouts when used in combination with stones used in the construction of masonry buildings is addressed (granite, schist and limestone), again considering different conditions (dry, wet and saturated). It is shown that the performance of the commercial products is rather different and careful selection of injection materials in practical applications is recommended.